The Australian Goverrnment's M&E System - Mackay, Keith (World Bank, Washington, DC, 2012)
Countries from all over the world have shown an interest in Australia's experience in creating a monitoring and evaluation (M&E) system that supports evidence-based decision making and performance-based budgeting. The Australian M and E system in existence from 1987-97 was generally considered to be one of the most successful and was driven by the federal Department of Finance (DoF). This note discusses the genesis, characteristics, and success of this particular system and briefly considers the Australian government's approach to M and E after the system was abolished. The contrast between these two periods provides many valuable insights into success factors and challenges facing successful M and E systems, and into implementing evidence-based decision making more broadly.